Pembelajaran Klinik Conference Melalui Tugas Outline Terhadap Hasil Belajar Metodologi Penelitian Pendidikan - Noor Aini; Sigit Prasetyo (UNIKA SANTU PAULUS RUTENG, 2018)
Many problems faced by students with research methods, many students are still confused about what method is used in their research. In addition, students need more knowledge about the research methodology, the types of research methods, the requirements of the researcher, the research steps and the benefits of the research. Therefore, it is necessary to do a learning model so that students are able to explore the material contained in the Educational Research Methodology, especially in mathematics learning. The subjects in this study were 5th semester PGMI students at UIN Sunan Kalijaga Yogyakarta. Data collection techniques consist of interviews, observations, posttest, and library research. This research is a type of qualitative descriptive research that describes the good student learning outcomes in the Educational Research Methodology course through outline assignments with conference learning clinical model.